OVERVIEW OF PEDAGOGIC COMPETENCE IN MASTERING PAUD LEARNING METHODS AT TKQ MATLAUL KHOIR - Naila Lutfiyatul; Rika Purnamasari (Journal of Pedagogical Content Knowledge, 2025)
This study aims to describe the pedagogical competence of teachers in mastering early childhood education (ECE) teaching methods at TKQ Matlalul Khoir. Pedagogical competence is an essential aspect that teachers must possess to plan, implement, and evaluate an effective learning process that aligns with the characteristics of young children. This research uses a descriptive qualitative approach and collects data through observation and interviews with one of the teachers. The results of this study show that the pedagogical competence of teachers at TKQ Matlalul Khoir is significantly good. They have implemented various teaching methods, such as learning through play, storytelling, singing, and project-based learning. However, there are some challenges that need to be addressed, such as limited learning aids and the diversity of children's characteristics in one class. To improve competence, continuous learning evaluations are held, as well as participation in seminars and training related to early childhood education. Thus, the application of good pedagogical competence is expected to support the optimal development of young children at TKQ Matlalul Khoir.